Peranan Self Regulation Di Tengah Konstelasi Industri Media Pada Harian Republika - Tania, Rizki; Alfiah, Dian; Septiarini, Lia; Irwansyah, Irwasnyah (Universitas Muhammadiyah Yogyakarta, 2018)
Regulation and Journalistic Code of Ethic plays an important role as a guide for professional journalists. Similarly, self-regulation that plays an important role as Principles, Code of Ethics, and Standards of Conduct for the press and media companies. The purpose of this research is to prove the theoretical concept of communication technology and media regulation on the role of self regulation in the media industry constellation in Republika's Newspaper. This research is a descriptive qualitative research with research resource is Executive Editor of Republika's Newspaper. Data collection techniques used in this study are interview techniques, literature study and documentation. Regarding the concept of regulatory study theory in the form of self regulation in the constellation of the media industry in general, the press has a duty in maintaining professionalism and integrity by complying with applicable regulations without any conflict of interest from any party. In supporting media regulation at state law level, high commitment by media company in applying its self regulation is required. And accompanied by awareness and control of the public in supervising media behavior to stay professional.Keywords: mass media, print media, media regulation, code of ethics, self regulation,journalistic code of ethic, self regulation, ethics of journalist behavior.